The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1021/ct049977a
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking the Conductor-like Polarizable Continuum Model (CPCM) for Aqueous Solvation Free Energies of Neutral and Ionic Organic Molecules

Abstract: The conductor-like polarizable continuum model (CPCM) using several cavity models is applied to compute aqueous solvation free energies for a number of organic molecules (30 neutral molecules, 21 anions, and 19 cations). The calculated solvation free energies are compared to the available experimental data from the viewpoint of cavity models, computational methods, calculation time, and aqueous pKa values. The HF/6-31+G(d)//HF/6-31+G(d) and the HF/6-31+G(d)//B3LYP/6-31+G(d) with the UAKS cavities, in which rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
795
3
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 1,046 publications
(855 citation statements)
references
References 64 publications
23
795
3
1
Order By: Relevance
“…The relative energy difference is calculated to be 0.6 kcal/mol very close to the 0.7 kcal/mol obtained using CPCM single point calculations. 22,36 Structures TS9 are similar to the most stable closed transition states located for the alkylation reaction of pyrrole with (E)-crotonaldehyde organocatalyzed by dimethylamine. 16 However, transition vector motion along the reaction coordinate of TS9 corresponds to a concerted asynchronous Diels-Alder cycloaddition reaction.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The relative energy difference is calculated to be 0.6 kcal/mol very close to the 0.7 kcal/mol obtained using CPCM single point calculations. 22,36 Structures TS9 are similar to the most stable closed transition states located for the alkylation reaction of pyrrole with (E)-crotonaldehyde organocatalyzed by dimethylamine. 16 However, transition vector motion along the reaction coordinate of TS9 corresponds to a concerted asynchronous Diels-Alder cycloaddition reaction.…”
Section: Resultsmentioning
confidence: 87%
“…Solvation energies of a representative group of neutral, anionic, and cationic molecules, are computed relatively well with this methodology. 22 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Takano et al have performed benchmarking studies for the solute-cavity descriptions within the CPCM solvation model for the prediction of acidity constants. They found that the UAKS cavity definition, which uses united atom radii optimized at the PBE1PBE/6-31G(d) level of theory, estimates the solvation free energies within ~10.5 kJ/mol of experimental solvation free energies [76].…”
Section: Solvationmentioning
confidence: 99%
“…Takano and Houk have previously shown 28 that HF-CPCM calculations with cavities determined with use of UAKS radii produce reliable results for the aqueous free energy corrections. Moreover, they observed that CPCM is faster when large molecules are involved, and more accurate than PCM.…”
Section: Calculation Of Oxygen Atom Transfer Free Energies In Aqueousmentioning
confidence: 99%